Perspectives for the production of bioethanol from macroalgae biomass - Paz Cedeno, Fernando Roberto [UNESP]; Solorzano Chavez, Eddyn Gabriel [UNESP]; de Oliveira, Levi Ezequiel; Gelli, Valéria Cress; Monti, Rubens [UNESP]; Masarin, Fernando [UNESP] (My University, 2018)
Ethanol is currently produced on large scale from sugarcane, corn (first-generationethanol) and lignocellulosic materials (second-generation-ethanol), which results in a competition for space for growing food products. Therefore, future limitations on the availability of land for agriculture may require a shift of focus from land resources to marine resources. It is known that some macroalgae are rich in carbohydrates and devoid of lignin. The structural polysaccharides of the macroalgal cell walls are formed by an external matrix of amorphous mucilage, which can be composed of polysaccharides, such as carrageenan, agar, and starch. In addition, macroalgal biomass also contains other components that provide rigidity to the cell walls, such as cellulose fibers and sodium carbonate. In all the studied species, the main monomeric sugars from the polysaccharides are glucose and galactose. The low lignin content in the macroalgal cell walls makes them less recalcitrant than terrestrial plants to chemical and enzymatic treatments, which makes polysaccharides more accessible. In addition, macroalgal cultures generally have a productivity between 5.8 and 16.8 kgm-2year-1, higher than terrestrial plants which is between 0.5 and 4.4 kgm-2year-1. The conversion of macroalgal biomass polysaccharides into fermentable monomeric sugars requires several processing steps. The main methods currently used are chemical and enzymatic, culminating in the hydrolysis of polysaccharides in monosaccharides. Carrageenophyta macroalgae are the best candidates for bioethanol production (third and forth generation-ethanol), since they present substantial amounts of carrageenan and glucans, which are formed by galactose and glucose, sugars that are easily fermentable by yeasts and bacteria.